Społeczna odpowiedzialność przedsiębiorstw Doliny Lotniczej w świetle badań empirycznych - Bembenek, Bogusław (Corporate Social Responsibility of Aviation Valley Enterprises in the Light of Empirical Research, 2009)
The author of this article presents some issues on corporate social responsibility conception based on theoretical and research studies. In the article the gist of the partnership Aviation Valley enterprises with key stakeholders is presented. The author stresses that this form of partnership may seriously stimulate increase of enterprises competitiveness.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 236-247